Potential Impacts of Artificial Intelligence (AI) in Biotechnology - Gomes, Alexandrina; Gonçalves, Beatriz; Inglês, Bruno; Silvério, Sara; Pinto, Carlos A.; Saraiva, Jorge A. (Applied sciences, 2024)
The impact of artificial intelligence (AI) in biotechnology has become increasingly significant, driving advancements across multiple subfields in several areas of science. The demand for faster data analysis, integration of extensive databases, pattern recognition, problem solving, and even hypothesis generation has fueled the development of AI technologies in subjects like modern biotechnology, which AI has revolutionized, where the main goal is to develop new advanced products and technologies through the manipulation of biological organisms. The main impacts of AI observed in biotechnology are focused on four colors of biotechnology: green (agricultural sector); red (health sector); white (industries); and blue (marine sector). Numerous AI tools have been developed and made freely available, significantly reducing researchers’ workloads. However, the application of AI in biotechnology also raises questions that must be addressed. This review exhibits and discusses the impacts of AI on biotechnology, the advantages and disadvantages of its current presence, and the potential ethical issues and social impacts.